FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI PRIA DALAM MENGGUNAKAN MOP (METODE OPERASI PRIA) DI DUSUN KRALAS DESA CANDEN KECAMATAN JETIS KABUPATEN BANTUL YOGYAKARTA 2017 - Titik Mariati (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
Background: Male steady contraception or vasectomy is a method of minor operative contraception in men who are very safe, simple and very effective, take short operative time and do not require general anesthesia. Vasectomy is a clinical procedure to stop male reproductive capacity by performing occlusion of vas deferens, thus inhibiting spermatozoa and no spermatozoa in cement / ejaculation (no delivery of spermatozoa from the testes to the penis). Level of education, Knowledge, perception, and access to services is an important factor in the formation of participation Male participation using MOP (Male Operation Method). Until now, direct male participation is still low despite the increase. In Kralas, active participants of  KB MOP in 2017 reached 0.68%. Objective: The aim of this stdy is to know the factors of affecting male participation in using MOP (male operation method) in Kralas Canden village Jetis district Bantul regency Yogyakarta. Metods: In this research use descriptive qualitative. Sampling studies using saturated sample to obtain the total sample of 47 people. Result: The result of chi-square test all variable operation method of man is education level influence with man participation result 0,0019 and p 0,05, knowledge influence with man participation result 0.000 and p 0,05, perception influence with man participation result 0.000 and p 0.05, access to care had an effect on male participation of 0.000 and p 0,05. Conclusion: There is a significant influence between the level of education, knowledge, perception, and access to male participation in using MOP (Male Operation Method) in Dusun Kralas Canden Village, Jetis District, Bantul Regency, Yogyakarta.